Pengaruh Pengawasan Terhadap Produktivitas Kerja Pegawai Kantor Inspektorat Kabupaten Kediri - Sinollah Sinollah; Hermawanto Hermawanto (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2020)
This study aims to: 1) To analyze the effect of performance appraisal on employee job satisfaction; 2). To analyze the effect of performance appraisal on employee performance, and 3). To analyze the effect of job satisfaction on the performance of structural employees receiving performance benefits at the Malang Regency Ministry of Religion. To achieve this goal, this research uses descriptive research type with quantitative approach and the questionnaire becomes the main instrument in data collection. The results of the study using path analysis showed that: 1). Performance appraisal variable has no significant effect on employee job satisfaction; 2). Performance appraisal variables affect employee performance, and 3). Job satisfaction variable has a significant effect on employee performance. For this reason, the Ministry of Religion is suggested to be able to implement a performance appraisal program well for employees so that employees can feel the benefits as feedback about various things such as abilities, strengths, weaknesses, and potential which in turn is beneficial for their performance. In addition, performance is something important that is influenced by satisfaction, for that employee job satisfaction is well guarded through an objective performance appraisal.